Algorithmic consumer culture. Issue 5 (3rd September 2022) - Airoldi, Massimo; Rokka, Joonas
ABSTRACT: This article conceptualizes algorithmic consumer culture, and offers a framework that sheds new light on two previously conflicting theorizations: that (1) digitalization tends to liquefy consumer culture and thus acts primarily as an empowering force, and that (2) digitalized marketing and big data surveillance practices tend to deprive consumers of all autonomy. By drawing on critical social theories of algorithms and AI, we define and historicize the now ubiquitous algorithmic mediation of consumption, and then illustrate how the opacity, authority, non-neutrality, and recursivity of automated systems affect consumer culture at the individual, collective, and market level. We propose conceptualizing "algorithmic articulation" as a dialectical techno-social process that allows us to enhance our understanding of platform-based marketer control and consumer resistance. Key implications and future avenues for exploring algorithmic consumer culture are discussed.